The Use of Quizizz to Develop Instructional PJBL Practices in Teaching Writing - Nurul Septi yani; Fahrur Rozi; Katharina Rustipa (Universitas Negeri Semarang, 2023)
This research aims to explain the use of Quizizz to develop instructional PJBL practices in teaching writing to the eighth-graders of MTs Ihsaniyah Balapulang, Tegal. This research applied mixed-methods research design and the concurrent embedded design. There were 30% quantitative data which were collected through students’ formative assessment and 70% qualitative data which were collected through observation, documents, and interview. This study involved an English teacher and 19 students of MTs.Ihsaniyah Balapulang. The instruments used were observation checklist, interview, documentation, and formative test. The researcherss did the validity, reliability, practicality, authenticity and T-test. The T-test result shows that the sig (2-tailed) value is 0.00 <0.05 and the t-count (5.759) > t-count (2.1009). Thus, it can be concluded that the hypothesis used in this study was accepted. It means that the use of Quizizz to develop instructional PJBL practices can be said to be effective. The teaching and learning observation in the classroom also show that the English teacher was able to effectively conduct the teaching of writing recount text, and the students were enthusiastic about participating in writing lessons using PJBL and Quizizz. Therefore, Quizizz and PJBL can be considered as an effective approach to improve students’ writing.